The Impact of Last Mile Delivery on Customer Satisfaction - Lindah Asiimwe (Uganda Christian University, 2023)
This dissertation delved into the intricate realm of last-mile delivery, a pivotal segment of the e-commerce supply chain, and its profound influence on customer satisfaction. In an era marked by the exponential growth of e-commerce, where customer satisfaction is a linchpin for business success, understanding the dynamics of last-mile logistics has become paramount. The study primarily focused on Glovo Uganda, an emerging player in the e- commerce and food delivery landscape, serving as a microcosm of the broader industry. The exponential growth of e-commerce has intensified the competition, making customer satisfaction a critical factor for business success. This study aimed to investigate the multifaceted relationship between last-mile delivery and customer satisfaction, with Glovo Uganda as the focal point. Understanding how the intricacies of last-mile logistics impact customer satisfaction is essential for both practitioners in the field and researchers seeking to contribute to the evolving landscape of e-commerce. The research employed a qualitative approach, utilizing structured questionnaires as the primary data collection method. These questionnaires were distributed among three key groups of participants: customers, delivery partners, and key stakeholders within Glovo Uganda. This methodology allowed for a comprehensive exploration of the subject matter, capturing diverse perspectives and experiences. The research objectives encompassed several dimensions of last-mile delivery, including the impact of delivery speed, the influence of accurate and reliable last-mile logistics, and the implementation and utilization of advanced technologies. This qualitative approach enabled an in-depth understanding of the interplay between these variables and their collective influence on customer satisfaction. By gathering insights from multiple stakeholders, this study aimed to provide a holistic view of the last- mile delivery ecosystem within Glovo Uganda. The findings of this study illuminated the intricate dynamics of last-mile delivery and its direct correlation with customer satisfaction. Delivery speed emerged as a crucial factor, with customers increasingly expecting swift and timely deliveries. Accurate and reliable last-mile logistics were identified as fundamental pillars in building customer trust and minimizing uncertainties in the delivery process. Additionally, the integration of advanced technologies, such as GPS tracking and real-time monitoring systems, showcased the potential to enhance delivery efficiency and reliability. However, this adoption also brought forth complexities related to privacy and regulation. Despite these challenges, the study concluded that aligning delivery strategies with evolving customer expectations, proactively addressing operational 5 challenges, and judiciously leveraging advanced technologies were imperative for Glovo Uganda's sustained success in the competitive e-commerce landscape. The recommendations extended to various stakeholders, emphasizing collaborative efforts to enhance last-mile delivery experiences. In conclusion, this dissertation contributed valuable insights to the e- commerce and logistics sectors, paving the way for more efficient and satisfying last-mile deliveries in the digital age.
This is a dissertation.